The Influence of Environmental Awareness, Consumer Attitude, and Price on Purchase Decisions of Eco-Friendly Products: A Study on Tessa Green Tissue Among Students of Universitas Muhammadiyah Surakarta - Rahmawati, Rahmawati; Wahyudi , Tri Nur (Dinasti Publisher, 2026)
This study employs a quantitative descriptive method and involves students of Universitas Muhammadiyah Surakarta who use or have the potential to use the eco-friendly product Tessa Green tissue. The purpose of this research is to determine and verify how environmental awareness, consumer attitude, and price influence their purchase decisions. The sample consists of 120 respondents selected using a purposive sampling technique through the distribution of a Google Form questionnaire. Data were analyzed using the Partial Least Square (PLS) method. The findings indicate that environmental awareness has a negative yet significant effect on purchase decisions, while consumer attitude and price have positive and significant effects. These results highlight an important insight that high environmental awareness does not necessarily lead individuals to prefer eco-friendly products, especially those related to daily necessities such as tissue. Furthermore, the study shows that price and psychological perception play a more crucial role than sustainability values, helping producers develop more effective marketing strategies to encourage consumers to purchase environmentally friendly products.